2015
DOI: 10.1111/cxo.12306
|View full text |Cite
|
Sign up to set email alerts
|

Near work‐induced transient myopia in Indian subjects

Abstract: Purpose: The aim was to determine the characteristics of near work-induced transient myopia (NITM) in asymptomatic Indian subjects and the influence of target size and contrast. Methods: Two studies were conducted: First, 24 myopes and 24 emmetropes viewed four targets (N8 and N12 with 50 and 90 per cent contrasts) placed at 0.2 m for five minutes. The refractive status was assessed objectively, before and after carrying out the near task, with the Grand Seiko WAM-5500 open-field autorefractor under monocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
2
11
1
Order By: Relevance
“…In Indian individuals with myopia, an initial posttask myopic shift of 0.21 D was observed for the initial NITM. 19 We presume that variation in age, degree of myopia, and duration of near work are factors that influence the initial magnitude of NITM.…”
Section: ) (D)mentioning
confidence: 99%
“…In Indian individuals with myopia, an initial posttask myopic shift of 0.21 D was observed for the initial NITM. 19 We presume that variation in age, degree of myopia, and duration of near work are factors that influence the initial magnitude of NITM.…”
Section: ) (D)mentioning
confidence: 99%
“…18 Other studies showed association of near work with increase in myopia. 19,20 The limitation of this study is that it is a crosssectional study where further follow up of patients was not done. Future studies will be carried out for a longer follow-up to determine the effect of smart phone usage upon the progression of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…All the participants with a variant myopic presentation had reduced accommodative facility values in both the eyes, though this was not statistically significantly different from the Indian clinical norms. [ 34 35 ] It is also well established in the literature that the accommodative characteristics in Indian eyes are different, especially low among myopes. [ 29 36 ]…”
Section: Discussionmentioning
confidence: 99%